Aggregation of Platelets Remaining in Circulation after Acute Thrombosis - Zbinden, G; Grimm, L; Muheim, M (Thrombosis and Haemostasis, 1971)
I.v. injection of ADP and Na laurate in guinea pigs caused acute platelet sequestration and occasional formation of fresh platelet thrombi in the lungs. ADP-induced aggregation of platelets isolated after the injection was found to be consistently reduced. No difference in platelet response to ADP was found when PRP obtained before and after treatment with Evans blue was compared. It was concluded that ADP- and Na laurate-induced thrombosis eliminated preferentially the ADP-responsive platelet fraction whereas the effect of Evans blue was not dependent on the functional state of the platelets.